Brain MRI Features of CSF Human Immunodeficiency Virus Escape. Issue 6 (5th August 2018) - Narvid, Jared; Callen, Andrew; Talbott, Jason; Uzelac, Alina; Dupont, Sara M.; Chow, Felicia; Price, Richard W.; Rehani, Bhavya
ABSTRACT: BACKGROUND AND PURPOSE: HIV infection of the central nervous system (CNS) is a nearly universal feature of untreated systemic HIV infection. While combination antiretroviral therapy (ART) that suppresses systemic infection usually suppresses CNS (CNS) HIV infection, exceptions have been reported with discordance between CSF and blood HIV RNA concentrations such that CSF demonstrates higher HIV concentrations than blood, referred to as CSF HIV escape. Rarely, CSF HIV escape presents with neurological symptoms, called neurosymptomatic escape. METHODS: In this report, we describe the MRI findings in 6 patients with neurosymptomatic escape who were identified at our institution. RESULTS: MR imaging suggests an encephalitis possibly evolving from a distinct HIV subpopulation within the CNS. A major difference between primary HIV infection and the current case series is that untreated HIV encephalitis usually occurs in the setting of late disease and a low CD4 whereas CSF Escape develops in setting of a higher CD4, as well as more robust immune and inflammatory responses. Our findings show a burden and distribution of white matter signal abnormalities atypical for patients adherent to ART and that differs from that seen in untreated HIV encephalitis and leukoencephalopathy. Moreover, these patients may also demonstrate perivascular enhancement, a finding not previously reported in the CSF HIV escape literature. CONCLUSION: Recognition of these imaging characteristics—patchy subcortical white matter intensities and a perivascular pattern of enhancement—may be helpful in recognition and, along with other clinical information and CSF findings, in diagnosis of neurosymptomatic escape.